1999
DOI: 10.1103/physrevlett.82.3176
|View full text |Cite
|
Sign up to set email alerts
|

Extreme In-Plane Anisotropy of the Heavy-HolegFactor in (001)-CdTe/CdMnTe Quantum Wells

Abstract: A paradoxical behavior of the linear polarization of luminescence has been observed in CdTe͞CdMnTe quantum wells. Although the polarization is induced by a magnetic field, neither the magnitude of the polarization nor the orientation of its plane vary when the field is rotated in the quantum well plane. An analysis shows that this can be accounted for by a low-symmetry perturbation of the crystal lattice that gives rise to a mixing of the valence subbands leading, in turn, to an anisotropy of the in-plane heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 18 publications
3
52
0
1
Order By: Relevance
“…We observe that as a general trend the isotropic hole g-factor g i hh is responsible for the fourth harmonic and the anisotropic g-factor g a hh is essential for the second harmonic. The latter was reported previously for magnetic QWs [8] and our findings follow the general trend of previous theoretical approaches [9]. We conclude that the very good agreement with experiment proves the validity of our approach.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We observe that as a general trend the isotropic hole g-factor g i hh is responsible for the fourth harmonic and the anisotropic g-factor g a hh is essential for the second harmonic. The latter was reported previously for magnetic QWs [8] and our findings follow the general trend of previous theoretical approaches [9]. We conclude that the very good agreement with experiment proves the validity of our approach.…”
supporting
confidence: 91%
“…This situation changes drastically for low dimensional heterostructures because of the complicated valence band structure. Kusrayev et al [8] observed * Electronic address: astakhov@physik.uni-wuerzburg.de a second spherical harmonic component (i.e., π-periodic oscillations under sample rotation) in the polarization of emission from narrow quantum wells (QWs). This result was explained in terms of a large in-plane anisotropy of the heavy-hole g-factor g xx hh = −g yy hh .…”
mentioning
confidence: 99%
“…The defects of these kinds are expected to be present in abundance as a result of the RTA treatment and original ternary composition of the barriers. Another possible reason of such a strong broadening in the narrow ADQWs is an inhomogeneous elastic stress, which represents an inherent property of the II-VI heterostructures and gives rise, e.g., to a strong in-plane PL anisotropy in II-VI QWs [17] or suppressed interwell exciton relaxation in semimagnetic ADQWs [4]. We suggest that it is a combination of both factors, which result in the strong inplain potential fluctuations and give rise to a very wide bands of localized excitons in the PL spectra ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The situation is more complicated for the Voigt measurements, as it is neither possible to assign the measured g factors to a specific carrier, nor to establish their sign: it is a priori not clear which of the two linearly polarized Zeeman splittings belongs to which transition. It has been shown for quantum wells [48] and ensembles of quantum dots [49] that the in-plane orientation of the linear polarization axis depends on the relative in-plane orientation of the electron and hole spin. Details of the hole state, such as light-hole intermixing and the nonlinear remote-band coupling of the magnetic field to the hole spin, can lead to the peculiar situation in which the in-plane orientation of the polarization axis depends nontrivially on the in-plane magnetic-field orientation [49].…”
Section: -8mentioning
confidence: 99%